Analysis of Grammatical Cohesion in Instagram Social Media Captions - Anindita, Widyashanti Kunthara (ELITE JOURNAL, 2025)
Language efficiency is key to clarity, especially in the context of social media platforms like Instagram. Other elements in captions from the official company accounts, (such as @hariankompas and @gojekindonesia, @goodlifebca and @traveloka. id, @pertamina) and personal accounts (such as @deddycorbuzier, @emildardak,@astridwidayani, @marissahaque, @radityadika). Differences in communicative patterns are to be investigated here by examining grammatical cohesion systems: reference, substitution, ellipsis and conjunction. The research enhances our understanding on the distinction between formal (business) and informal (personal) language strategies and their implications for readability and audience reception. The aims of the study are: (1) to find out which grammatical coherence types are more frequently employed in the corporate and personal Instagram captions; (2) to establish if there are differences between these two account types, concerning their use of grammatical coherence. The study employs qualitative method with the use of discourse analysis. Captions from five official company and five personal accounts are utilized in collecting the data. Halliday and Hasan's (1976) model is then used to identify and classify grammatical cohesion items before similarities and differences are identified through a comparative descriptive analysis. It is anticipated that the findings will offer a thorough understanding of the language techniques that define both personal and professional Instagram communication.